Quaternary ice sheets and sea level regression drove divergence in a marine gastropod along Eastern and Western coasts of South America - Fernandez Iriarte, P. J.; Gonzalez-Wevar, C. A.; Segovia, N.; Rosenfeld, S.; Hune, M.; Fainburg, L.; Nunez, J. D.; Haye, P. A.; Poulin, E. (My University, 2020)
The southern coastline of South America is a remarkable area to evaluate how Quaternary glacial processes impacted the demography of the near-shore marine biota. Here we present new phylogeographic analyses in the pulmonate Siphonaria lessonii across its distribution, from northern Chile in the Pacific to Uruguay in the Atlantic. Contrary to our expectations, populations from the southwestern Atlantic, an area that was less impacted by ice during glacial maxima, showed low genetic diversity and evidence of recent expansion, similar to the patterns recorded in this study across heavily ice-impacted areas in the Pacific Magellan margin. We propose that Atlantic and Pacific shallow marine hard-substrate benthic species were both affected during the Quaternary in South America, but by different processes. At higher latitudes of the southeast Pacific, ice-scouring drastically affected S. lessonii populations compared to non-glaciated areas along the Chile-Peru province where the species was resilient. In the southwest Atlantic, S. lessonii populations would have been dramatically impacted by the reduction of near-shore rocky habitat availability as a consequence of glacio-eustatic movements. The increase of gravelly and rocky shore substrates in the southwest Atlantic supports a hypothesis of glacial refugia from where the species recolonized lower latitudes across the Atlantic and Pacific margins. Our results suggest that current patterns of genetic diversity and structure in near-shore marine benthic species do not solely depend on the impact of Quaternary glacial ice expansions but also on the availability of suitable habitats and life-history traits, including developmental mode, bathymetry and the likelihood of dispersal by rafting.
Keywords: Last Glacial Maximum; Ice age